Experimentally validated CFD simulations predicting wind effects on photovoltaic modules mounted on inclined surfaces. (December 2018) - Chowdhury, Mohammed Gofran; Goossens, Dirk; Goverde, Hans; Catthoor, Francky
Highlights: Wind tunnel experiments and CFD simulations were used to investigate the effect of air gaps and cavities in PV constructions. Narrow air gaps result in low near-surface wind speeds over a PV module. Wall cavities do not affect the magnitude of the wind speed at the top or back surface of a PV module. Wall cavities generate an increased deflection of the wind towards the lateral sides of a PV module. Abstract: Computational Fluid Dynamics (CFD) and wind tunnel experiments were used to study wind flow over PV modules attached to inclined surfaces. Wind velocities were investigated at various positions on a test module, for five wind speeds varying from 1 to 5 m s −1 . After validation the CFD model was used to study the effects air gaps and wall cavities under the module have on the airflow over the module. Data were measured for two air gaps, 3.5 cm and 5.5 cm thick, and for three cavity depths ranging from 0 cm to 9 cm. The 3.5 cm air gap resulted in lower near-surface wind speeds over the PV module. This will result in less wind-generated cooling of the module, and consequently, in a lower electrical performance. The wall cavities did not affect the magnitude of the wind speed over the module but generated an increased deflection of the wind towards the lateral sides of the module. They also created clockwise and anti-clockwise eddies next to the PV setup and in the cavity itself. The study shows that in CFD simulations for PV applications, even small irregularities in the PV setup should be included in the model to predict reliable results.